Peningkatan Hasil Belajar Peserta Didik dengan Media Audiovisual pada Peserta Didik Kelas III Sekolah Dasar - Novita Sari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to improve student learning outcomes using audio-visual media in third grade students of SD N 1 Taratak Baru. This type of research is Classroom Action Research (CAR). This study uses a spiral model. The study consisted of 4 procedures, namely planning, implementing actions, observing, and reflecting. The subjects of this study were the third grade students of SD N 1 Taratak Baru, totaling 23 students. This research was carried out in three cycles/cycles. The implementation of each plot/cycle is carried out using audio-visual media. Collecting data in this study using test and observation methods. The research instrument used was in the form of a question sheet description and observation sheet of students and teachers. The data analysis technique used in this study was carried out with qualitative data analysis techniques and quantitative data analysis. The results of data analysis from this study showed that the students; learning mastery of 23 students turned out to be 12 people with a percentage of 52.1% categorized in the moderate level of mastery, 3 people with a percentage of 13% categorized in the medium level of mastery, 6 people with a presentation of 26% categorized in the low level of mastery, 2 people with a percentage of 8.69% were categorized in the very low level of mastery.